A contemporary systematic literature review of enogastronomic experiences - Mikinac, Krešimir (Oeconomica Jadertina, 2023)
Enogastronomic experiences are on the rise in the tourism industry, and the number of tourists travelling primarily to experience food and wine culture has increased. In addition, destination marketing organisations are increasingly using local food and wine as a differentiator when marketing a destination. Despite the growing interest in this field of tourism, there is a paucity of research on the importance and impact of enogastronomic tourism on a destination’s image. This study thus comprises a systematic literature review on these topics, summarising the current state of knowledge on these areas and highlighting the potential for future research. The purpose of this research is comprehensively presents the literature on enogastronomic experiences using descriptive statistics and cluster analysis. This paper reports on findings from a review of 85 peer-reviewed studies that focused on enogastronomic tourism from 2012 to 2023. The findings reveal evolving trends in this field of study, namely, the VOSviewer program was applied to identify the most frequently used keywords associated with the enogastronomic tourism and the most active countries in publications. To provide an even deeper understanding of this topic, future research should also include other research areas in which enogastronomy has been studied to provide an overview of interdisciplinary perspectives. In addition, further examination of the dependent and independent variables is recommended to understand what predictors and consequences of the enogastronomic experience are.
Keywords: enogastronomy, experience, cluster analysis, literature review